Economic assessment of traditional surgical intervention versus use of a new innovative radiofrequency based surgical system in device replacements - Kypta, Alexander; Blessberger, Hermann; Kammler, Juergen; Nahler, Alexander; Neeser, Kurt; Lichtenauer, Michael; Edlinger, Christoph; Kellermair, Joerg; Kiblboeck, Daniel; Lambert, Thomas; Auer, Johannes; Steinwender, Clemens (PloS one, 2018)
Intra-operative complications like mechanical damages to the leads, infections and hematomas during generator replacements of implantable pacemakers and defibrillators contribute to additional costs for hospitals. The aim of this study was to evaluate operation room use, costs and budget impact of generator replacements using either a traditional surgical intervention (TSI) with scissors, scalpel and electrocautery vs. a new radiofrequency energy based surgical system, called PEAK PlasmaBladeTM (PPB). We conducted a retrospective analysis of a population including 508 patients with TSI and 254 patients with PPB who underwent generator replacement at the Kepler University Hospital in Linz or the St. Josef Hospital in Braunau, Austria. The economic analysis included costs of resources used for intra-operative complications (lead damages) and of procedure time for TSI vs. PPB. Proportion of males, mean age and type of generator replaced were similar between the two groups. Lead damages occurred significantly more frequent with TSI than with PPB (5.3% and 0.4%; p< 0.001) and the procedure time was significantly longer with TSI than with PPB (47.9±24.9 and 34.1±18.1 minutes; p<0.001). Shorter procedure time and a lower rate of lead damages with PPB resulted in per patient cost savings of €81. Based on estimated 2,700 patients annually undergoing generator replacement in Austria, the use of PPB may translate into cost savings of €219,600 and 621 saved operating facility hours. PPB has the potential to minimize the risk of lead damage with more efficient utilization of the operating room. Along with cost savings and improved quality of care, hospitals may use the saved operating room hours to increase the number of daily surgeries.